Pengaruh Penerapan Growth Mindset Terhadap Kecerdasan Emosional Melalui Self-Motivation Di Lingkungan Akademik - Najwa Parawansa; Ebit Gregorius Gultom; Wida Safitri; Azizah Aulia Nisa; M. Surya dilaga (Pusat Riset dan Inovasi Nasional, 2023)
Self-motivation is one of the main success factors whose implementation is still being questioned in various academic environments in Indonesia. This quantitative study aims to obtain information on the profile of self-motivation skills of students at Sultan Ageng Tirtayasa University and influence class level on self-motivation skills. This research involved 50 students who were positioned as research subjects. Data on self-motivation skills was collected using an integrated critical thinking skills rubik questionnaire. The data collected used descriptive statistics in the form of averages and analytical statistics in the form of Chi-Square. The results of this research inform that the self-motivation skills profile of students at Sultan Ageng Tirtayasa University is still in the low category. Furthermore, class level has a significant effect on the self-motivation skills have a significant level. Following up on the research findings at this time, the self-motivation empowerment of students at Sultan Ageng Tirtayasa University must be further optimized through designing growth mindset plans, learning resources and self-motivation-based learning assessments.